Inequalities and patience in catching up - Kazumichi Iwasa; Laixun Zhao (Asian Development Bank Institute (ADBI), 2017)
This paper examines how impatience interacts with inequalities in economic development. We consider two distinct groups of households (i.e., with intrinsic inequality), and show that (i) under decreasing marginal impatience (DMI), an unequal society may be preferable for poor households; (ii) poor households tend to benefit more from positive shocks under DMI than constant marginal impatience; (iii) inequality exhibits a sharp inverted-U shape as more people become rich, which should be good news for developing countries in catching up; and (iv) a tax on capital income reduces poor households' income when the fraction of the rich is sufficiently small. We also extend the basic model to examine the effects of immigration into rich countries.
Keywords: 330; People's Republic of China; India; inequality; catching up; marginal impatience